Functional and structural connectivity of the amygdala in obsessive-compulsive disorder - Rus, Oana Georgiana (Neuroimage Clin, 2016)
BACKGROUND: The amygdala is known to be involved in anxiety processing, but its role in the psychopathology of obsessive-compulsive disorder (OCD) is still unclear. AIMS: In this MRI study we investigated potential alterations in structural and functional connectivity of the amygdala in 42 adult patients with OCD and 37 healthy subjects. METHOD: Psychophysiological interaction analysis was used to explore amygdala functional connectivity during a negative affective task. Probabilistic tractography was then employed to study structural connectivity and integrity of underlying white matter fiber tracts. RESULTS: Compared to controls, OCD patients showed a significantly increased functional connectivity of the left amygdala with mostly parieto-occipital regions during task. No structural connectivity differences could be found between the groups. In addition, only patients showed a significant association between functional and structural connectivity of these regions. Moreover, symptom severity was negatively associated with structural integrity of the underlying white matter tracts. CONCLUSIONS: Present results emphasize the relevance of the amygdala for OCD and may reflect that neuronal alterations in structural connectivity could be associated with functional connectivity alterations in broader networks.